An open web-based platform for enhancing the visibility of Brazilian research - Da Cruz, Alvaro Magri Nogueira [UNESP]; Santos, Adriana Barbosa [UNESP]; De Souza, Rogeria Cristiane Gratao [UNESP]; Parolin, Thiago Luiz [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2020)
The scientific research developed in Brazil is prominent in the global scene. Despite this, it still lacks visibility outside the scientific sphere and better recognition for Brazilian researchers. This paper presents a web-based platform proposed to reinforce the open access initiatives to expand scientific knowledge. It is focused on publishing research articles by audiovisual format. The audiovisual resources can introduce another dynamic for scientific communication in Brazil. The characteristics and subcharacteristics of the ISO/IEC25010 quality model were adapted to define the platform's design, its architecture and user interface.
Keywords: scientific communication; scientific production; scientific-learning video; video article; web application